Effect of Feeding Decorticated Tamarind (Tamarindus indica) Seed Based Diet on Intake, Nutrient Digestibility and Growth Performance in Mandya Sheep - M. S. Shilpa; T. M.Prabhu; H. S.Madhusudhan; M.D.Gouri; K .B.Sathisha; K. M.Rashmi (Indian Journal of Animal Nutrition, 2024)
A feeding cum digestion trial of twelve weeks duration was taken up to study the effect of feeding partially and completely decorticated tamarind seed based diet on intake, nutrient digestibility and growth performance in Mandya sheep. Eighteen Mandya lambs of about 3-4 months of age with body weight ranging from 6 to 10.5 kg were distributed to three treatments of six each in a completely randomized design. The animals of Treatment 1 (T1) received a compounded feed mixture (CFM) having 30% wheat bran (WB) (control), whereas, Treatment 2 (T2) and Treatment 3 (T3) received CFM with 15% partially decorticated tamarind seeds (PDTS) and 15% completely decorticated tamarind seeds (CDTS) substituting 50% wheat bran in control CFM, respectively. Sorghum (COFS-29) hay was fed ad libitum as a sole source of roughage for the lambs in all the treatments. Chemical composition analyses (%) revealed that both PDTS and CDTS were comparable with wheat bran. Rumen in vitro net gas (ml/200mg/24h) production and energy density (ME, MJ /Kg DM) were similar between the control and test feedstuffs (WB 12.39, PDTS 12.82 and CDTS 12.81 ME, MJ/Kg DM). The difference among the groups in terms of total DMI (as ‘g’ per day, per cent of body weight and g/kg W0.75) through CFM and the sorghum (COFS-29) hay was not significant (P≥0.05). However there was significant (P≤0.05/ P≤0.01) difference in OM, EE and ADF intake. The ADG (g) was statistically significant between T1 & T2 as well as T1 & T3 (T1 - 54.16, T2 - 73.42 and T3 - 65.68). There was significant (P≤0.05/ P≤0.01) difference among the three groups in DM, OM and NDF digestibility, whereas the digestibility of other nutrients was comparable. The per cent digestible organic matter in dry matter (DOMDM) (T1-65.49, T2-63.88 and T3-70.97) was also statistically significant (P≤0.01) among the treatment groups. Considering the overall results, it is inferred that the partially decorticated tamarind seed meal could be used as an alternative feedstuff to replace cereal byproduct in compounded feed mixture of ruminants.